Breakthroughs in the development of regional leading sectors: challenges and sustainability - Nur, Andi Cudai; Aslinda, Aslinda; Guntur, Muhammad; Didin, Didin (Linguistics and Culture Review, 2021)
The purpose of this research is to identify, analyze, explain the essence and orientation of regional-based tourism development as a leading sustainable sector. The approach used is qualitative and quantitative techniques. The results showed that as one of the leading sectors in the Sinjai area is tourism, considering that the tourism potential in Sinjai is quite potential seen from three aspects, namely: 1) natural tourism potential consisting of 35 natural attractions scattered from each district, 2) historical potential and regional culture consisting of 71 tourist destinations, 3) man-made tourism potential and special interest. Tourism in Sinjai has taken a toll on the Co-19 pandemic so that the impact is quite concerning for the local government and local communities. Is there still the government's support and interest in developing the tourism sector, which is a challenge in its sustainability. It takes creativity, innovation and breakthroughs by the government in absorbing various changes and technological advances for future life.